Catching the wind - Dobson, Melanie (Tyndale House Publishers, Inc., 2017)
When Daniel Knight was thirteen, he and ten-year-old Brigitte Berthold escaped the Gestapo agents who arrested both their parents. They survived a harrowing journey from Germany to England, only to be separated upon their arrival. For more than seventy years he has vowed to find Brigitte. Now a wealthy old man, his final hope in finding Brigitte rests with Quenby Vaughn, an American journalist working in London. Quenby is wary at the idea of teaming up with Daniel's lawyer, Lucas Hough, but the lure of Brigittes story is too much to resist. They follow a trail of deception, sacrifice, and healing that could change all of their futures.